2021
DOI: 10.21874/art-5-2022-01-19-61e8631b4c10b
|View full text |Cite
|
Sign up to set email alerts
|

Teletrabalho na atualidade: quais são os impactos no desempenho profissional, bem-estar e contexto de trabalho?

Abstract: A partir da pandemia imposta pelo novo coronavírus, o teletrabalho mostrou-se uma alternativa de arranjo de trabalho promissora e desejável em tempos de isolamento social, de forma que tem recebido atenção cada vez mais prioritária nas agendas de pesquisas em gestão de pessoas no setor público. O Serviço Federal de Processamento de Dados (Serpro) foi um dos pioneiros na utilização do teletrabalho no Brasil e, portanto, foi escolhido como lócus do estudo. Esta pesquisa levantou os pontos positivos e negativos d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 27 publications
0
3
0
4
Order By: Relevance
“…On the other hand, the flexibility of working from home is highlighted as one of the positive points for those who fit into this work modality, with some professionals reporting well-being (VILARINHO; PASCHOAL; DEMO, 2021;BATTISTI et al, 2022), higher quality of life (AGUIAR et al, 2022;BARROS;SILVA, 2010;FILARDI;CASTRO;ZANINI, 2020) and better professional performance (AGUIAR et al, 2022;VILARINHO;PASCHOAL;DEMO, 2021). In the research by Aguiar et al (2022), the research participants expressed greater satisfaction with the remote work regime even when there was mention of overload due to excessive tasks at home.…”
Section: Reflections On Compulsory Teleworking In the Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the flexibility of working from home is highlighted as one of the positive points for those who fit into this work modality, with some professionals reporting well-being (VILARINHO; PASCHOAL; DEMO, 2021;BATTISTI et al, 2022), higher quality of life (AGUIAR et al, 2022;BARROS;SILVA, 2010;FILARDI;CASTRO;ZANINI, 2020) and better professional performance (AGUIAR et al, 2022;VILARINHO;PASCHOAL;DEMO, 2021). In the research by Aguiar et al (2022), the research participants expressed greater satisfaction with the remote work regime even when there was mention of overload due to excessive tasks at home.…”
Section: Reflections On Compulsory Teleworking In the Pandemicmentioning
confidence: 99%
“…This research is in the context of a case study at the Federal Data Processing Service (Serpro) and the Federal Revenue Service. Also, a case study within the scope of Serpro, Vilarinho, Paschoal, and Demo (2021) found a perception of an increase in the quality of life of teleworkers.…”
Section: Reflections On Compulsory Teleworking In the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Além do aspecto econômico, ele também define o seu status perante a sociedade e é caracterizado como sendo a a própria identidade pessoal. A simples presença da concessão de oportunidades que lhe são asseguradas configura-se um valor simbólico e de grande valor afetivo, aumentando de forma bastante considerável o seu bem-estar físico e emocional (VILARINHO et al, 2021).…”
Section: Saúde E Bem-estar Dos Trabalhadoresunclassified
“…No mesmo seguimento, Tamoyo e Pascoal (2003), relatam que de nada adianta haver uma pré-disposição de seus colaboradores, dotados de conhecimento e vontade para empreender, se a empresa da qual ele faz parte não apresenta as ferramentas necessárias para a sua devida aplicação. Trabalhadores que não são estimulados e valorizados, não há uma boa relação de troca, e, portanto, são explorados (VILARINHO et al, 2021).…”
Section: Saúde E Bem-estar Dos Trabalhadoresunclassified